Gender : sociological perspectives. - Lindsey, Linda L (Routledge, 2021)
"A landmark publication in the social sciences, Linda Lindsey's Gender is the most comprehensive textbook to explore gender sociologically, as a critical and fundamental dimension of a person's identity, interactions, development, and role and status in society. Ranging in scope from the everyday lived experiences of individuals to the complex patterns and structures of gender that are produced by institutions in our global society, the book reveals how understandings of gender vary across time and place and shift along the intersecting lines of race, ethnicity, culture, sexuality, class and religion. Arriving at a time of enormous social change, the new, seventh edition extends its rigorous, theoretical approach to reflect on recent events and issues with insights that challenge conventional thought about the gender binary and the stereotypes that result. Recent and emerging topics that are investigated include the #MeToo and LGBTQ-rights movements, political misogyny in the Trump era, norms of masculinity, marriage and family formation, resurgent feminist activism and praxis, the gendered workplace, and profound consequences of neoliberal globalization. Enriching its sociological approach with interdisciplinary insight from feminist, biological, psychological, historical, and anthropological perspectives, the new edition of Gender provides a balanced and broad approach with readable, dynamic content that furthers student understanding, both of the importance of gender and how it shapes individual trajectories and social processes in the U.S. and across the globe"--